PELAKSANAAN PEMBELAJARAN KETERAMPILAN BED COVER DI PKBM SITI NURBAYA KOTA PADANG - Wiwid Zuryani (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2014)
The background of this research is the high participation of the residents in the program learn skills of "bed cover", where at the program implementation seen is serious on student in accepting and listening of learning materials by tutors. The purpose of this study is to describe the implementation of learning skills "bed cover" in "PKBM Siti Nurbaya, Kelurahan Batang Arau, Kecamatan Padang Selatan. as seen from the aspect of learning objectives, learning materials, learning methods, learning environment and the benefit of programs. This research is designed as descriptive quantitative research. The research subjects are the residents learner of "bed cover" skill in "PKBM Siti Nurbaya, Kelurahan Batang Arau Kecamatan Padang Selatan. The result of this research is most of the learners stated that they've already known about the learning objectives, learning materials, learning methods, learning environment and benefit programs of learning the "bed cover" skill.